The impacts of Covid-19 on household behavior and household waste in Turkey - Yalcinyigit, Serap; Donmez-Turan, Aygul; Akbas, Halil E.; Varank, Gamze (UNIVERSITA DEGLI STUDI DI TORINO, 2022)
COVID-19 has caused many radical changes in our daily life. The main purpose of this study is to examine the impact of the pandemic on household behavior and waste changes in the largest city of Turkey, Istanbul. Research data were collected from 946 participants in the period May to December 2020 through an online survey, and frequency and logistic regression analyses were conducted. Frequency analysis of the data showed that mask, glove, disposable bag usage, cooking at home, online shopping, home delivery, dishwasher and washing machine usage increased, while ordering food from outside decreased. In line with these behavioral changes, we found that medical, food, disposable bag and plastic wastes generated by the sampled households increased as well. We then conducted logistic regression analysis to examine the correlation between changes in household behavior and waste disposal and the income and size of households during this pandemic period. The empirical findings highlight the importance of developing special management strategies for medical, food and plastic wastes and for households with different socio-economic backgrounds to reduce the unsustainable environmental impact of COVID-19.
Keywords: Covid-19; Household Behavior; Household Income; Household Size; Household Waste; SOLID-WASTE; ATTITUDES; Science & Technology - Other Topics; Environmental Sciences & Ecology